2019
DOI: 10.1088/1755-1315/275/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

A review on the use of drones for precision agriculture

Abstract: In recent years, there has been a strong activity in the so-called precision agriculture, particularly the monitoring aspect, not only to improve productivity, but also to meet demand of a growing population. At a large scale, precise monitoring of cultivated fields is a quite challenging task. Therefore, this paper aims to propose a survey on techniques, applied to precision agriculture monitoring, through the use of drones equipped with multispectral, thermal and visible cameras. For each application, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(68 citation statements)
references
References 16 publications
0
65
0
3
Order By: Relevance
“…Specifically, low-cost light UAVs dotted with RGB cameras are the most preferred Unmanned Aerial System (UAS) by many users, farmers among others. Whereas RGB cameras are limited by the development of spectral products, beyond scouting and monitoring, DSMs avoid artefacts that appear often in the UAV imagery, such as shadows projected from objects in the surface or clouds, light differences during the flight time or different colours caused by soil moisture or wet vegetation [38][39][40]. These challenges can be addressed with deep learning, but they need a large labelled database to feed the algorithm [41].…”
mentioning
confidence: 99%
“…Specifically, low-cost light UAVs dotted with RGB cameras are the most preferred Unmanned Aerial System (UAS) by many users, farmers among others. Whereas RGB cameras are limited by the development of spectral products, beyond scouting and monitoring, DSMs avoid artefacts that appear often in the UAV imagery, such as shadows projected from objects in the surface or clouds, light differences during the flight time or different colours caused by soil moisture or wet vegetation [38][39][40]. These challenges can be addressed with deep learning, but they need a large labelled database to feed the algorithm [41].…”
mentioning
confidence: 99%
“…UAVs have become a common tool in precision agriculture [66,67]. Thanks to their affordability, user-friendliness and versatility, UAVs are often the primary choice for fast and precise in situ remote sensing or survey operations.…”
Section: Uavs Remote Sensing Techniques and Sensorsmentioning
confidence: 99%
“…In a review study by Mogili [ 8 ], the researchers reported that drones can be used in pesticide and fertilizer application, so that humans do not come in contact with the some of these pesticides, which are harmful, and are gradually being phased out. Drones can also function as water sprinkling systems [ 8 , 36 ].…”
Section: Related Literaturementioning
confidence: 99%